2021
DOI: 10.11159/icsta21.109
|View full text |Cite
|
Sign up to set email alerts
|

Inference in Cardiovascular Modelling Subject to Medical Interventions

Abstract: Pulmonary hypertension (PH), i.e., high blood pressure in the lungs, is a serious medical condition that can damage the right ventricle of the heart and ultimately lead to heart failure. Standard diagnostic procedures are based on right-heart catheterization, which is an invasive technique that can potentially have serious side effects. Recent methodological advancements in fluid dynamics modelling of the pulmonary blood circulation system promise to mathematically predict the blood pressure based on non-invas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
0
0
Order By: Relevance
“…An earlier proof-of-concept study [2] has demonstrated the importance of closed-loop data science in cardio-vascular modelling. In that study, the detailed structure of the vasculature related to small blood vessels was approximated by electrical circuit elements (so-called ``Windkessel elements") to simplify the mathematical complexity.…”
Section: Extended Abstractmentioning
confidence: 99%
“…An earlier proof-of-concept study [2] has demonstrated the importance of closed-loop data science in cardio-vascular modelling. In that study, the detailed structure of the vasculature related to small blood vessels was approximated by electrical circuit elements (so-called ``Windkessel elements") to simplify the mathematical complexity.…”
Section: Extended Abstractmentioning
confidence: 99%